2011
DOI: 10.1002/cncr.26043
|View full text |Cite
|
Sign up to set email alerts
|

Providing developmentally appropriate psychosocial care to adolescent and young adult cancer survivors

Abstract: To deliver developmentally appropriate psychosocial care, the key developmental tasks facing adolescents and young adults (AYA) need to be taken into consideration. These include establishing autonomy from parents; a personal set of values and identity; strong peer relationships, including intimate and sexual relationships; and obtaining adequate preparation to join the workforce. To minimize the amount of disruption caused by the cancer experience and to maximize the health-related quality of life of AYA pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
260
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(274 citation statements)
references
References 28 publications
5
260
0
5
Order By: Relevance
“…Thompson et al proposed a model of cfc that includes a transitional care plan, monitoring for recurrence and late effects, and assistance with getting back to "normal" 17 . Other authors have identified the need for financial assistance for young adult cancer survivors 18,19 .…”
Section: Resultsmentioning
confidence: 99%
“…Thompson et al proposed a model of cfc that includes a transitional care plan, monitoring for recurrence and late effects, and assistance with getting back to "normal" 17 . Other authors have identified the need for financial assistance for young adult cancer survivors 18,19 .…”
Section: Resultsmentioning
confidence: 99%
“…Although many AYA patients have developed decision‐making skills regarding their own health or life goals,22 others will still look to others to help them with decision making and indeed they may return to a state of dependency when faced with cancer 23. Health‐related information should be delivered in a manner that is appropriate to the age of the patient because this is critical in helping AYA individuals learn to cope with their disease and navigate the health care system 24. The capacity to handle new situations is closely related to the concept of coping.…”
Section: Discussionmentioning
confidence: 99%
“…185 AYA men and women go through developmental stages marked by rapid changes in cognitive and emotional growth, and these issues need to be considered while delivering developmentally appropriate psychosocial and supportive care to AYA patients. 186 Few measurement tools have been developed to better understand health-related quality of life in AYA patients with cancer. 6 Palmer et al 187 developed an AYA Oncology Psychosocial Screening Tool to assist clinicians in supporting psychosocial coping during active treatment and promoting healthy post-treatment survivorship in AYA patients.…”
Section: Psychosocial and Behavioral Issuesmentioning
confidence: 99%
“…Reinforcing relationships with family, peers, and health professionals is an important aspect of life for AYA patients. 186,212 Although some studies have identified family support and cohesiveness as important contributors to a survivor's adjustment, others have identified the important role played by same-aged peers (healthy peers as well as other AYA cancer survivors) in helping AYA patients cope with cancer and overcome feelings of loneliness. 11,186 In one study, AYA patients with cancer (16-22 years of age) identified social support (including family members, friends, healthcare providers, and other patients) as their major coping strategy.…”
Section: Relationshipsmentioning
confidence: 99%